Distinct localisation of lipids in the ovarian follicular environment - Tawiwan Pantasri (2018)
© CSIRO 2015. Obesity is associated with decreased pregnancy rates due, in part, to compromised oocyte quality. The aim of the present cross-sectional study of 84 women undergoing oocyte aspiration was to: (1) compare insulin, lipids and glucose in follicular fluid with serum; (2) determine whether increased body mass index (BMI) and waist circumference, hyperinsulinaemia, dyslipidaemia or metabolic syndrome altered follicular fluid metabolites; and (3) determine relative lipid content in oocytes to reveal any influence of these parameters on oocyte quality and IVF outcomes. Insulin, glucose, triglyceride and free fatty acids were lower in follicular fluid than blood and not strictly correlated between compartments. Insulin, glucose and triglyceride positively correlated with increasing BMI and waist circumference in blood and follicular fluid. Insulin increased in follicular fluid in association with metabolic syndrome. Free fatty acid composition analysis showed saturated fatty acids, particularly palmitic and stearic acid, to be more prevalent in follicular fluid than blood. There were no associations between follicular fluid metabolites or oocyte lipid content and clinical outcomes; however, oocyte immaturity correlated with follicular fluid glucose and fatty acid levels, as well as metabolic syndrome. The present study confirms that the human ovarian follicular environment surrounding the oocyte exhibits a unique metabolite profile compared with blood, with distinct localisation of lipids within follicular fluid and oocytes.